INTERPRETATION OF THE LEGEND OF TRISTAN AND ISOLDE IN THE LYRICS OF THE SILVER AGE AS SINGLE PARADIGM - Alexandrina G. Klyus (Вестник Северо-Кавказского федерального университета, 2022)
This article analysis the interpretation of the legend of Tristan and Isolde in the lyrics of the Silver Age. The author focuses on the analysis of the functioning of medieval legends in russian literature. Compares lyrics of M. Kuzmin, Gabriak, G. Ivanov, F. Sologub, V. Ivanov.